Urgency of Law Enforcement in the Field of Conservation of Living Natural Resources and Ecosystems - Purnawati, Andi; Irmawaty, Irmawaty; Haling, Syamsul; Ikbal, Moh (Jurnal Dinamika Hukum, 2021)
Environmental law as a branch of legal science today plays an important role. Why not, human life and survival naturally and naturally will be largely determined by the upholding of laws in the field of the environment. One of the impacts of human selfishness and greed for the environment is the depletion of living natural resources and their ecosystems without regard to environmental balance and ecological principles. The method used in this study is a normative research type using primary, secondary, and tertiary legal sources. The nature of explanatory research with a dogmatic and theoretical approach. Analysis of legal issues material uses deductive-inductive analysis techniques on legal issues that are the target of analysis through legal reasoning and argumentation. Researchers found that to support the implementation and enforcement of laws in the field of conservation of living natural resources and their ecosystems, cross-sectoral coordinative mechanisms in an integrated and stimulating manner are more activated. The frequency between related sectoral agencies is increased to reduce law violations in the field of conservation of living natural resources and their ecosystems.Keywords: Law Enforcement, Natural Resources, Conservation